2020
DOI: 10.1016/j.lfs.2020.118035
|View full text |Cite
|
Sign up to set email alerts
|

Long non-coding RNA TINCR as potential biomarker and therapeutic target for cancer

Abstract: Despite the recent scientific advances made in cancer diagnositics and therapeutics, cancer still remains the second leading cause of death worldwide. Thus, there is a need to identify new potential biomarkers/molecular targets to improve the diagnosis and treatment of cancer patients. In this regard, long non-coding RNAs (lncRNAs), a type of non-coding RNA molecule, have been found to play important roles in diverse biological processes, including tumorigenesis, and may provide new biomarkers and/or molecular… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
36
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 54 publications
(43 citation statements)
references
References 87 publications
1
36
0
Order By: Relevance
“…Tissue Differentiation-Induced Non-Coding RNA TINCR is highly expressed in keratinocytes and is essential for normal epidermal differentiation (206). It is a 3,733-nucleotide long transcript located on chromosome 19p13 (207). Aberrant TINCR expression has been implicated in multiple human cancers.…”
Section: Colon Cancer Associated Transcriptmentioning
confidence: 99%
“…Tissue Differentiation-Induced Non-Coding RNA TINCR is highly expressed in keratinocytes and is essential for normal epidermal differentiation (206). It is a 3,733-nucleotide long transcript located on chromosome 19p13 (207). Aberrant TINCR expression has been implicated in multiple human cancers.…”
Section: Colon Cancer Associated Transcriptmentioning
confidence: 99%
“…Long noncoding RNAs (lncRNAs) are a subtype of ncRNAs that are >200 nucleotides in length [ 13 , 14 , 61 , 62 , 63 ], and several have been implicated in the development and progression of breast cancer [ 31 ]. LncRNAs can act as promoters or suppressors during breast cancer progression via molecular mechanisms that include modulating cellular proliferation, invasion, apoptosis, and drug resistance [ 12 , 14 ].…”
Section: Noncoding Rnas (Mirnas and Lncrna) And Their Aberrant Expression In Er-positive Breast Cancermentioning
confidence: 99%
“…Long non-coding ribonucleic acids (RNAs) (lncRNAs), which consist of more than 200 nucleotides, are involved in protein translation and messenger RNA (mRNA) decay, which play important roles in regulating inflammatory pathways (16,17). A growing number of studies has revealed that some lncRNAs participate in the pathogenesis of multiple diseases, including cancer, ocular alkali burns, and Sjögren's syndrome by regulating mRNA directly or indirectly (18)(19)(20). Long non-coding ribonucleic acids regulate gene expression through epigenetic regulation, transcriptional regulation, and post-transcriptional regulation, thus participating in various biological processes (BP) such as cell proliferation, differentiation, and apoptosis (21)(22)(23)(24)(25)(26).…”
Section: Introductionmentioning
confidence: 99%